Adjuvantation of Kyasanur Forest Disease vaccine with TLR9 agonist CpG adjuvant enhances immunological efficacy and potency of the vaccine - Chandranaik B. Marinaik; Bharath T. Lakshmikanth; Chinmayie K. Siddaramegowda; Apsana Rizwan; Amitha Reena Gomes; Keerthi Kaje; Doddamane Rathnamma; Shrikrishna Isloor; Archana M; Jagadish Hiremath; Raveendra Hegde (PLoS ONE, 2025)
The present study was carried out with the objectives of formulation of Kyasanur Forest Disease (KFD) vaccine adjuvanted with TLR9 agonist, CpG; evaluation of cell mediated and humoral immune response of CpG adjuvanted KFD vaccine in mice. The KFD seed virus (P9605) procured from ICMR-National Institute of Virology, Pune was used for the preparation of KFD vaccine and was confirmed by Real Time Reverse Transcription-PCR. The KFD vaccine prepared in chick embryo fibroblast primary culture was inactivated with 0.1% of formalin. Safety test was performed to assess the safe does of CpG adjuvant in mice. The KFD vaccine adjuvanted with 10 µg of CpG per dose of vaccine was formulated and immunologically evaluated in mice. Evaluation of humoral immune response (HIR) by mouse protection test showed that CpG when used as an adjuvant, significantly (P < 0.0001) enhances HIR in mice with better survival percentages when compared to the non-adjuvanted KFD vaccine. The cell mediated immune response/cytokine response evaluated by quantifying Interferon-ϒ (IFN-ϒ), Tumour Necrosis Factor-Alpha (TNF-α) and IL-12 production using ELISA showed that CpG significantly (P < 0.001) increases IFN-ϒ, TNF- α and IL-12 when used as an adjuvant in KFD vaccine in mice. The potency test showed that CpG adjuvanted vaccine has higher protective efficacy with better protective index compared with the non-adjuvanted KFD vaccine. Taken together these findings, the study recommends CpG as an adjuvant in the formalin inactivated KFD vaccine since the adjuvantation was safe and enhanced KFD specific immunogenicity and protective efficacy in mice.